Physical oral care prevents ventilator-associated pneumonia in Vietnam: A prospective interventional study. Issue 12 (December 2022) - Saito, Sho; Thao, Pham Thi Ngoc; Ishikane, Masahiro; Xuan, Phan Thi; Kutsuna, Satoshi; Dai, Huynh Quang; Ohtsu, Hiroshi; Kimura, Tomomi; Kiyohara, Hiroyuki; Shimada, Yasuyuki; Maruoka, Yutaka; Thuy, Pham Thi Phuong; et al.
Abstract: Background: Ventilator-associated pneumonia (VAP) has emerged as a critical issue in the intensive care unit (ICU) because of its high burden on patients and medical staff. Here, we examined the potential for reducing VAP incidence through physical oral care interventions without any medication. Methods: This prospective interventional study compared VAP incidence during an 8-month baseline period (usual oral care) and a 9-month intervention period (physical oral care with sponge brush) among patients who received mechanical ventilation for >48 h in a tertiary care hospital in Vietnam from 2017 to 2019. Physical oral care was provided by general ICU nurses who had been trained by dentists and infection control nurses. VAP was diagnosed using the Clinical Pulmonary Infection Score. Results: In total, 423 patients were enrolled in the baseline group and 454 patients were enrolled in the intervention group; 303 and 300 patients, respectively, were included in the analysis. Two hundred thirty-eight VAP episodes were identified: 135 (44.6%) during the baseline period and 103 (34.3%) during the intervention period. Univariate analysis revealed significant reduction of VAP occurrence in the intervention period (odds ratio = 0.65; 95% confidence interval = 0.47–0.90; P = 0.010). The incidences of VAP per 1000 ventilator-days were 63.4 (135/2128) during the baseline period and 48.4 (103/2128) during the intervention period ( P = 0.038). Conclusions: Physical oral care without any medication (e.g., chlorhexidine) reduced VAP incidence in the ICU. This method could be used to reduce VAP incidence, particularly in countries with limited medical resources.